2004
DOI: 10.1002/erv.552
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder not otherwise specified (EDNOS): profiles of clients presenting at a community eating disorder service

Abstract: Objective: A substantial proportion of eating disorder presentations receive a DSM-IV diagnosis of eating disorder not otherwise specified (EDNOS), yet research comparing EDNOS with anorexia nervosa (AN) and bulimia nervosa (BN) is limited. The aim of this study was to further investigate EDNOS in clients at a UK Community Eating Disorder Service. Method: The Eating Disorder Examination (EDE) was used to generate DSM-IV diagnoses. Clinical profiles of EDNOS clients are compared with those of patients with AN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 7 publications
9
93
1
1
Order By: Relevance
“…Fairburn and Bohn 17 have suggested that this is due to the misconceptions that EDNOS is rare and that EDNOS is mild. Contrary to these beliefs, recent findings have indicated that EDNOS represents 60% of all eating disorder cases that present to outpatient services [18][19][20] and 40% of patients that present to tertiary care services. 21 In addition, the duration and severity of EDNOS is similar to AN and BN.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Fairburn and Bohn 17 have suggested that this is due to the misconceptions that EDNOS is rare and that EDNOS is mild. Contrary to these beliefs, recent findings have indicated that EDNOS represents 60% of all eating disorder cases that present to outpatient services [18][19][20] and 40% of patients that present to tertiary care services. 21 In addition, the duration and severity of EDNOS is similar to AN and BN.…”
Section: Introductionmentioning
confidence: 70%
“…21 In addition, the duration and severity of EDNOS is similar to AN and BN. [19][20][21][22] The transdiagnostic model and treatment of eating disorders conceptualizes AN, BN, and EDNOS as a single unitary diagnostic category. 23 This is based on the fact that there are important similarities between the three groups (e.g., weight-related self-evaluation, dietary restraint, bingeing, vomiting) and that migration between diagnostic categories is common.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-documented that subthreshold eating disorder diagnoses are prevalent among individuals presenting for outpatient eating disorders treatment and are associated with clinically significant levels of impairment (10,11). Thus, bipolar patients meeting the following empirically supported eating disorder not otherwise specified (EDNOS) criteria were included in the ED group: 1) All DSM-IV criteria for BN except the frequency of binge eating and purging is less than 2/week (12) (n = 1); or 2) Objective binge episodes occurring 1/week on average for at least 6 months in the absence of purging or other recurrent compensatory behaviors (13) (n = 8).…”
Section: Participantsmentioning
confidence: 99%
“…6 Perhaps secondary to these challenges in applying the current eating disorder diagnoses to younger patients, descriptive clinical studies indicate that EDNOS is the most common eating disorder in clinical settings. [7][8][9][10] This diagnosis is problematic due to its heterogeneity, rendering the amount of specific information conveyed by the EDNOS label to be minimal. This problem is not unique to youth -as EDNOS similarly predominates in adult clinical samples 11 -but the reasons younger patients are assigned this diagnosis may be distinct as suggested by the Workgroup.…”
Section: Introductionmentioning
confidence: 99%